Angled-tip vs. straight-tip guidewire in ERCP: a randomized, multicenter study. (4th May 2023) - Hausmann, Johanes; Lefa, Foteini; Filmann, Natalie; Eickhoff, Axel; Zeuzem, Stefan; Herrmann, Eva; Tantau, Marcel; Albert, Jörg
Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is the mainstay for interventional treatment of biliopancreatic diseases, and guidewires are decisive for successful treatment. Methods: A randomized, multicenter, open-label study was conducted in patients in whom a guidewire was required in ERCP. Success rate and duration of the investigation were evaluated by randomly applying hydrophilic guidewires with a straight tip (ST) or an angled tip (AT) configuration, with normal (type NF) or enhanced (type EF) flexibility. Randomization was stratified by indication, i.e., stricture of the intra-hepatic bile ducts, stricture of the extrahepatic bile ducts, obstruction by bile duct stones, or interventions involving the pancreas. Cross-over was allowed if the initially allocated guidewire did not result in treatment success. Results: Four hundred fifty-three patients were included, and 422 were finally analyzed. In 363 procedures (86%), the initially allocated wirés use resulted in treatment success. The success rate for using a guidewire with an angled tip configuration was 87.5 vs. 79.9% in a straight tip configuration ( p = 0.049), and in negotiating an intrahepatic stricture the success rate was 90.7 vs. 69.1%, respectively ( p = 0.008). No significant differences were observed in other indications. Procedural duration time did not differ in between the treatment groups. Conclusion: ERCP guidewires with an angled tip were more frequently successful when compared to straight tipped wires and most successful in treating intrahepatic strictures. Guidewires with standard vs. enhanced tip flexibility showed equal success rates in all indications.